1/3(z+4)-6=2/3(5-z)=

Simple and best practice solution for 1/3(z+4)-6=2/3(5-z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/3(z+4)-6=2/3(5-z)= equation:



1/3(z+4)-6=2/3(5-z)=
We move all terms to the left:
1/3(z+4)-6-(2/3(5-z))=0
Domain of the equation: 3(z+4)!=0
z∈R
Domain of the equation: 3(5-z))!=0
z∈R
We add all the numbers together, and all the variables
1/3(z+4)-(2/3(-1z+5))-6=0
We calculate fractions
(3z(-)/(3(z+4)*3(-1z+5)))+(-6zz/(3(z+4)*3(-1z+5)))-6=0
We calculate terms in parentheses: +(3z(-)/(3(z+4)*3(-1z+5))), so:
3z(-)/(3(z+4)*3(-1z+5))
We add all the numbers together, and all the variables
3z0/(3(z+4)*3(-1z+5))
We multiply all the terms by the denominator
3z0
We add all the numbers together, and all the variables
3z
Back to the equation:
+(3z)
We calculate terms in parentheses: +(-6zz/(3(z+4)*3(-1z+5))), so:
-6zz/(3(z+4)*3(-1z+5))
We multiply all the terms by the denominator
-6zz
Back to the equation:
+(-6zz)
We get rid of parentheses
3z-6zz-6=0
We move all terms containing z to the left, all other terms to the right
3z-6zz=6

See similar equations:

| 2(6-2x)+6=-9x-6+5x | | 2x+4-3x=-1 | | 15r+r-13+r=20 | | 8r-7=7 | | Nx3=-4 | | (-4+5b)=16 | | 3x+(2-4x)=0 | | d+58=180 | | 12*y=72 | | 3-2g=- | | 2x+5+7x-14=180 | | -1.3+y/7=18.8 | | 20x2-6x=-8 | | 6w+5=17 | | g÷2=4 | | 3.4x-19.1=9.1 | | -8x-63=0.25-3 | | a+58=180 | | 243=3^x+3 | | 2,3d=6 | | 3t^2+14t+16=0 | | 22=11/12a | | 10=2/5w | | 49=4r+9 | | 5+-2n=91+1 | | 3(w-67)=12 | | 3+x+24=28x | | 0=3t^2+14t+16 | | 70x=75x^2 | | w/3-14=19 | | 16q+4q-11q-q-7q=12 | | -7(w-97)=70 |

Equations solver categories